Antimicrobial efficacy and cytotoxicity of ethanolic extracts of Salvia officinalis and Juglans regia against oral pathogens - Sara Ghadaksaz; Safar Farajnia; Fatemeh Pournaghiazar; Hamed Ebrahimzadeh Leylabadlo; Reza Salahlou; Abbas Delazar; Amir Zandesh (Journal of Advanced Periodontology and Implant Dentistry)
Background. Herbal extracts have gained attention for their potential benefits in promoting oral health and preventing dental caries and periodontal diseases. This study evaluated the antimicrobial effects and cytotoxicity of ethanolic extracts of Salvia officinalis and Juglans regia, both individually and in combination, against Streptococcus mutans, Lactobacillus casei, and Candida albicans, microorganisms associated with oral diseases. Methods. In this in vitro study, the hydroalcoholic (ethanolic) extracts of J. regia and S. officinalis were prepared using the maceration method. To determine the antimicrobial effectiveness, the zone of inhibition in the disk agar diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were assessed for each extract, separately and in combination. The extracts’ cytotoxicity was investigated at their effective doses using the MTT (methyl thiazole tetrazolium) assay. Results. Compared to the negative control, ethanolic extracts of S. officinalis and J. regia exhibited a significant inhibitory effect (P<0.001) on S. mutans and L. casei. Salvia officinalis extract exhibited antimicrobial activities, as evidenced by the MIC values of 237.5 µg/mL for S. mutans, 118.7 µg/mL for Lactobacillus casei, and 31.25 mg/mL for C. albicans. The ethanolic extract of Juglans regia exhibited MIC values of 29.6 µg/mL for S. mutans, 475 µg/mL for L. casei, and 15.62 mg/mL for C. albicans, respectively. MTT assay results showed that the extracts had no cytotoxic effects at the MIC on the L929 cell line; however, pure chlorhexidine was toxic at 0.2% concentration. Conclusion. The study results revealed that the ethanolic extracts of S. officinalis and J. regia and their combined application showed antimicrobial activity against pathogenic microorganisms pertinent to oral health. In addition, cytotoxicity evaluations indicated that these extracts are non-toxic to the L929 cell line at effective concentrations.